Intermittent hypoxia at rest for improvement of athletic performance - Bärtsch, P.; Dehnert, C.; Friedmann-Bette, B.; Tadibi, V. (Scandinavian Journal of Medicine & Science in Sports, 2008)
Two modalities of applying hypoxia at rest are reviewed in this paper: intermittent hypoxic exposure (IHE), which consists of hypoxic air for 5-6 min alternating with breathing room air for 4-5 min during sessions lasting 60-90 min, or prolonged hypoxic exposure (PHE) to normobaric or hypobaric hypoxia over up to 3 h/day. Hypoxia with IHE is usually in the range of 12-10%, corresponding to an altitude of about 4000-6000 m. Normobaric or hypobaric hypoxia with PHE corresponds to altitudes of 4000-5500 m. Five of six studies applying IHE and all four well-controlled studies using PHE could not show a significant improvement with these modalities of hypoxic exposure for sea level performance after 14-20 sessions of exposure, with the exception of swimmers in whom there might be a slight improvement by PHE in combination with a subsequent tapering. There is no direct or indirect evidence that IHE or PHE induce any significant physiological changes that might be associated with improving athletic performance at sea level. Therefore, IHE and PHE cannot be recommended for preparation of competitions held at sea level.